Cooperative Learning Through BlackBoard: Students’ Perceptions on Teamwork and Soft Skills Required to Manage an Event - A Case Study of The Edventure of Aladdin - Siti Hafizah, Daud; Nurien Hidayu, Muhammad Rusly (INTI International University, 2018)
Event management education has emerged as an alternative to the related disciplines of business, tourism and hospitality. Numerous courses offered in the area of event management has raised questions on employability of graduates in requiring the students to be employed in the industry. This article explores a study offering a multifaceted perspective on the requisite skills and abilities students perceive to be associated with event management employment. By employing students’ experiences and perspectives over the individual leadership and soft skills. This study employed 179 structured questionnaires and students’ individual reflections. Based on the findings, the respondents agreed that positive feedback on teamwork and communication skill, project management, ability to perform and personal attitudes are significant in organizing an event. For soft skills, the study found that communication, teamwork, creative thinking, time management, event management and self-management are the skills needed to be improved in the future.